2021
DOI: 10.1177/1724600821997461
|View full text |Cite
|
Sign up to set email alerts
|

The role of single nucleotide polymorphisms of miRNAs 100 and 146a as prognostic factors for prostate cancer

Abstract: Introduction: Prostate cancer has a high incidence in men and is the second cause of cancer death among americans male. microRNA (miR) is becoming a potential new prognostic factor for prostate cancer. Single nucleotide polymorphisms (SNPs) are common polymorphisms, characterized by a single exchange of nitrogen based in the DNA. This polymorphism is present in the miRs, altering their function. Objective: To evaluate the role of SNP rs1834306 of miR100 and rs2910164 of miR146a in the development and prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The dysregulation of the expression of a miRNA can be due to mutations in its coding genes or in their regulatory regions; for example, SNPs in miR-146a and in miR-100 have been identified that act as a factor of bad and an improved prognosis in PCa. In addition, it has been mentioned that these polymorphisms could alter miRNA function ( 19 ). Furthermore, it has been observed that mutations can affect the biogenesis of the mature miRNA while it is in the ‘seed’ region of the passenger strand, thus decreasing its expression ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of the expression of a miRNA can be due to mutations in its coding genes or in their regulatory regions; for example, SNPs in miR-146a and in miR-100 have been identified that act as a factor of bad and an improved prognosis in PCa. In addition, it has been mentioned that these polymorphisms could alter miRNA function ( 19 ). Furthermore, it has been observed that mutations can affect the biogenesis of the mature miRNA while it is in the ‘seed’ region of the passenger strand, thus decreasing its expression ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, there has been considerable interest in the potential clinical value of miRNAs in PCa [18], especially by our research group [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Eedunuri et al (2015) [7] showed that miR-137 negatively regulates the three genes comprising the p160 family.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous studies have investigated the associations between SNPs in miRNA genes and the risks of various types of cancer [25][26][27][28][29][30]. Although conflicting and inconsistent results have been obtained, the differences in association among studies may be due to different dietary habits, environmental exposures, and most importantly, different genetic background among the various study populations.…”
Section: Discussionmentioning
confidence: 99%